Prevalence Of Peptic Ulcer In Patients Of Liver Cirrhosis Presenting With Upper Gi Bleed - TanveerHussainMuhammadSarfraz,HaseebUrRehman,UzmaBatoolKashifIrfan, TanveerHussainMuhammadSarfraz,HaseebUrRehman,UzmaBatoolKashifIrfan (Journal of Rawalpindi Medical College, 2019)
BACKGROUND: Although major cause of upper GI bleed in patients of liver cirrhosis is variceal bleed. However a significant proportion also presents with non-variceal bleeding (NVB). AIM: The aim of study is to determine the frequency of peptic ulcers in patients of liver cirrhosis presenting with upper GI bleed. METHODS: This descriptive cross sectional study was conducted in Gastroenterology section of medicine department at Benazir Bhutto Hospital from April 2017 to December 2018 . 672 patients of liver cirrhosis presenting with upper GI bleed were enrolled in study through non probability consecutive sampling. Upper GI endoscopy of all patients was performed by consultant Gastroenterologist and findings were documented on standardized Performa. RESULTS: 672 patients were included in study with mean age of 54.68 ±11.15. Among these 370 (55.1%) were males and 302 (44.9%) were females. 92 patients (13.1%) had peptic ulcer as cause of upper GI bleed. 112 patients (16.6%) had both peptic ulcer and variceal bleed as cause of Upper GI Bleed and endoscopic findings of remaining 468 patients (69.6 %) showed varices (oesophageal + gastric) as prime source of bleeding. CONCLUSIONS: In this study, peptic ulcer accounted for 13.1 % of all cases of UGI bleeding. Keywords: Peptic Ulcer, Variceal bleeding, Upper GI bleed, Cirrhosis.